Aleksandr Bogdanov’s Concept of Culture: From Workers’ Circles to the Proletkult Movement - Scherrer Jutta (Cultural Science)
This paper analyses the historical genesis of Aleksandr Bogdanov’s conception of proletarian culture. In particular, the author deals with Bogdanov’s activity during his exile in Vologda, his organization of the Vpered group, and the debates over cultural politics amongst Russian Marxism in emigration. The systematic focus of the paper is on the concept of culture as based on the material and non-material capacities of the comprehension and the working and living conditions of the worker. The role of art in a system of culture is another important systematic focus of this analysis.